Comparative Efficacy of Topical Tacrolimus Versus Hydrocortisone in the Management of Atopic Dermatitis - Misbakh Ud Din, Muhammad Tahir, Ayesha Kanwal, Asma Khan, Attiya Munir, Aiman Asif, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Atopic dermatitis is a chronic, relapsing inflammatory skin condition that significantly impacts quality of life. Conventional management with topical corticosteroids, such as hydrocortisone, is effective but associated with potential adverse effects, including skin atrophy. Tacrolimus, a topical calcineurin inhibitor, offers a steroid-sparing alternative with a favorable safety profile. Objectives: To compare the efficacy and safety of topical tacrolimus 0.1% ointment versus hydrocortisone 1% cream in the management of atopic dermatitis. Study Design & Setting: Randomized controlled trial conducted at PAF Hospital Rafiqui PAF Base Rafiqui Shorkot cantt. Methodology: A total of 120 patients aged 18–60 years with clinically diagnosed atopic dermatitis were randomized into two equal groups. Group A received tacrolimus 0.1% ointment, and Group B received hydrocortisone 1% cream, both applied twice daily for 4 weeks. Efficacy was assessed using Eczema Area and Severity Index (EASI) and Visual Analog Scale (VAS) for pruritus at baseline and week 4. Adverse effects were recorded at each visit. Results: At week 4, mean EASI scores were significantly lower in the tacrolimus group (5.1 ± 1.9) compared to the hydrocortisone group (7.0 ± 2.1; p < 0.001). Percentage reduction in EASI was greater with tacrolimus (64.5 ± 10.3%) versus hydrocortisone (50.2 ± 11.6%; p < 0.001). Tacrolimus also showed greater reduction in VAS scores (2.6 ± 1.1 vs. 3.5 ± 1.2; p < 0.001). Burning sensation was more common with tacrolimus, while skin atrophy occurred only with hydrocortisone. Conclusion: Tacrolimus was more effective and had a better long-term safety profile than hydrocortisone, making it a suitable option for sensitive skin areas and prolonged therapy. Keywords: Adverse effects, Atopic dermatitis, EASI score, Hydrocortisone, Pruritus, Tacrolimus, Topical therapy